Platelet-to-hemoglobin ratio and stroke prognosis in older adults: a nonlinear and inflammation-mediated association - Luwen, Huang; Yu, Liu; Ming, Yu; Lei, Xu (Frontiers in Medicine, 2025)
BackgroundThe platelet-to-hemoglobin ratio (PHR) has been suggested as a prognostic biomarker in several diseases, but its relevance to short-term outcomes in older patients with acute ischemic stroke (AIS) remains uncertain. This study aimed to assess the association between the PHR and 3-month unfavorable outcomes in AIS patients.MethodsWe analyzed data from 1,470 older patients with AIS admitted to Seoul National University Hospital between 2010 and 2016. The primary outcome was a 3-month unfavorable outcome, defined as a modified Rankin scale score ≥3. The associations between the PHR and unfavorable outcomes were assessed using multivariable logistic regression. Receiver operating characteristic (ROC) curve analysis and bootstrap mediation analysis were also conducted.ResultsA total of 462 older patients (31.43%) experienced unfavorable outcomes. A nonlinear relationship between the PHR and patient prognosis was identified. While no significant association was observed below a threshold of 1.217, the risk of unfavorable outcomes increased significantly beyond this threshold (OR = 1.479; 95% CI: 1.158, 1.888). The area under the ROC curve for the PHR was 0.59 (95% CI, 0.558, 0.622), which was greater than that of the platelet count or hemoglobin alone in predicting unfavorable outcomes. Subgroup analysis revealed that the association was stronger in patients with hyperlipidemia. Bootstrap mediation analysis further revealed that high-sensitivity C-reactive protein (hs-CRP) partially mediated the relationship between PHR and adverse outcomes.ConclusionA nonlinear association was identified between the PHR and 3-month unfavorable outcomes in older patients with AIS. Subgroup analysis revealed that this association was more significant in patients with hyperlipidemia. Furthermore, mediation analysis indicated that hs-CRP partially mediated this relationship. These findings support the potential utility of the PHR as a practical biomarker for early prognostic stratification in AIS patients.